The Effects of Dividend Taxes on Equity Prices: A Re-examination of the 1997 U.K. Tax Reform. - Bond, S; Klemm, A; Devereux, M (SBS (University of Oxford), 2007)
We re-examine the extent to which personal taxes on dividends are capitalised into the equity prices of domestic firms, using data from around the time of the 1997 UK dividend tax reform, which removed a significant tax credit for an important group of investors: UK pension funds. The tax-adjusted CAPM suggests that the impact should depend on an average of dividend tax rates across all investors, and that UK pension funds should reduce their holdings of the previously tax-favoured asset: UK equities. Given that UK pension funds are small relative to the total size of the world capital market, a small open economy-type argument implies that the main effect of the reform would be to reduce UK pension funds’ ownership of UK equities, with little impact on the price of UK equities. We present evidence which is consistent with these hypotheses. We discuss why previous research (Bell and Jenkinson, 2002) reached the different conclusion that this tax reform had a large negative impact on UK share prices.